Spectrum of chronic gastrointestinal diseases with final outcome in children at a tertiary care centre: a single-centre study - Seerat, Iqtadar; Muhammad Atique,; Eitzaz Uddin Khan, (Journal of the Pakistan Medical Association, 2022)
Chronic gastrointestinal (GI) diseases in children present with a wide range of symptoms. Limited resources in Paediatric Gastroenterology in developing countries like Pakistan cause considerable difficulties in managing children with chronic GI diseases in a timely fashion. This retrospective descriptive study aimed to determine the spectrum and outcomes of chronic GI diseases in children. The study was conducted at the Paediatric Gastroenterology and Hepatology Department, Pakistan Kidney and Liver Institute & Research Centre (PKLI &RC) in Lahore. The duration of the study was from August 2019 to August 2020. A total of 40 children below the age of 15 years with chronic GI diseases were included. The diagnosis was principally established with the assistance of esophagogastroduodenoscopy and ileo-colonoscopy. ---Continue